Social autopsy: INDEPTH Network experiences of utility, process, practices, and challenges in investigating causes and contributors to mortality - Yevoo Lucy; Nielsen Rikke; Williams Thomas N; Kadobera Daniel; Källander Karin; Mutebi Aloysius; Akpakli Jonas; Narh Clement; Gyapong Margaret; Amu Alberta; Waiswa Peter (BMC, 2011)
Abstract Background Effective implementation of child survival interventions depends on improved understanding of cultural, social, and health system factors affecting utilization of health care. Never the less, no standardized instrument exists for collecting and interpreting information on how to avert death and improve the implementation of child survival interventions. Objective To describe the methodology, development, and first results of a standard social autopsy tool for the collection of information to understand common barriers to health care, risky behaviors, and missed opportunities for health intervention in deceased children under 5 years old. Methods Under the INDEPTH Network, a social autopsy working group was formed to reach consensus around a standard social autopsy tool for neonatal and child death. The details around 434 child deaths in Iganga/Mayuge Health and Demographic Surveillance Site (HDSS) in Uganda and 40 child deaths in Dodowa HDSS in Ghana were investigated over 12 to 18 months. Interviews with the caretakers of these children elicited information on what happened before death, including signs and symptoms, contact with health services, details on treatments, and details of doctors. These social autopsies were used to assess the contributions of delays in care seeking and case management to the childhood deaths. Results At least one severe symptom had been recognized prior to death in 96% of the children in Iganga/Mayuge HDSS and in 70% in Dodowa HDSS, yet 32% and 80% of children were first treated at home, respectively. Twenty percent of children in Iganga/Mayuge HDSS and 13% of children in Dodowa HDSS were never taken for care outside the home. In both countries most went to private providers. In Iganga/Mayuge HDSS the main delays were caused by inadequate case management by the health provider, while in Dodowa HDSS the main delays were in the home. Conclusion While delay at home was a main obstacle to prompt and appropriate treatment in Dodowa HDSS, there were severe challenges to prompt and adequate case management in the health system in both study sites in Ghana and Uganda. Meanwhile, caretaker awareness of danger signs needs to improve in both countries to promote early care seeking and to reduce the number of children needing referral. Social autopsy methods can improve this understanding, which can assist health planners to prioritize scarce resources appropriately.